P110 TOFACITINIB is associated with an impaired function of NK cells and a defective immunosurveillance against B-cell lymphomas. (21st February 2018) - Nocturne, G; Pascaud, J; Ly, B; Tahmasebi, F; Boudaoud, S; Seror, R; Stimmer, L; Mariette, X
Abstract : Introduction: Patients with rheumatoid arthritis (RA) are exposed to an increased risk of lymphoma and the impact of treatments is difficult to assess. Tofacitinib, an oral Janus Kinase (Jak) 3 and 1 inhibitor that has shown positive results in RA patients, may impair NK-cell function due to its inhibitory action on IL2 and IL15 signalling. Objectives: Given the fact that NK cells have been recently shown to participate to anti–lymphoma immunosurveillance, we aimed to assess if tofacitinib might impact NK-cell function and anti-lymphoma activity in vitro and in vivo in BAFF transgenic mice (a model of B cell autoimmunity associated with an increased risk of lymphoma). Methods: We have studied the consequences of in vitro exposure of NK to tofacitinib (10, 50 and 100 nM) or to DMSO (vehicle) during 6 days in presence of IL-2 (200 UI/ml): phenotype has been studied and then cytotoxicity against 2 non-Hodgkin B-cell lymphoma cell lines [Farage (EBV+) and SU-DHL4 (EBV-)] was assessed. In addition, BAFF transgenic mice were treated for 6 months with tofacitinib (2.25 mg/kg/d n=11; 4.5 mg/kg/d n=10) or vehicle (PEG: DMSO, n=6). Incidence of lymphoma was assessed by histologic examination using a composite score. Results: Firstly, we did not observe difference concerning the survival of NK cells in presence of tofacitinib or vehicle after 6 day culture. Secondly, we observed that culture in presence of tofacitinib was associated with a decreased level of activation with a dose effect. In addition, we observed a decreased expression of activating receptors such as NKp30, NKp44 and NKG2D. Last, we found that tofacitinib blocked NK cell maturation as observed with the significant decreased expression of CD57 on NK cells exposed to tofacitinib at 50 and 100 nM. These phenotypic abnormalities were associated with an impaired function of NK as assessed by co-culture: degranulation and cytotoxicity were significantly decreased after exposure to tofacitinib. In BAFF transgenic mice, the crude mortality and incidence of lymphoma did not differ between the 3 groups of treatment. Conclusions: This study demonstrates that tofacitinib treatment negatively impact the state of activation, maturation and functions of NK cells. These defects were not associated with a higher incidence of lymphoma in BAFF Tg mice after 6 months of exposure. However, this negative impact of tofacitinib on NK cells might participate to the increased risk of herpes zoster infection in patients treated with tofacitinib and suggest to remains cautious about a possible increased risk of lymphoma. Disclosure of interest: None declared